2021
DOI: 10.1002/mar.21574
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 on consumer evaluation of authentic advertising messages

Abstract: This study investigates the relationship between the COVID‐19 threat and consumer evaluation of a product with authenticity appeals in advertisements. We propose that threatening situations like COVID‐19 motivate consumers to lower their uncertainty and increase their preference for products with authentic advertising messages. Because individuals react differently to threatening environments according to their early‐life experiences, commonly reflected in childhood socioeconomic status, we examined whether ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 61 publications
(118 reference statements)
1
35
0
1
Order By: Relevance
“… Yu et al, 2021 , Ninaus et al, 2021 , Torrès et al, 2021 . Emotional Responses(Yellow) Trust, Risk Perception, Perceived Threat, Collaboration, Chen et al, 2021 , Yost and Cheng, 2021 , Park et al, 2022 . Consumer Behaviors(Brown) Consumer Behavior, Accountability, Digital Transformation, Retailing.…”
Section: Research Themesmentioning
confidence: 99%
“… Yu et al, 2021 , Ninaus et al, 2021 , Torrès et al, 2021 . Emotional Responses(Yellow) Trust, Risk Perception, Perceived Threat, Collaboration, Chen et al, 2021 , Yost and Cheng, 2021 , Park et al, 2022 . Consumer Behaviors(Brown) Consumer Behavior, Accountability, Digital Transformation, Retailing.…”
Section: Research Themesmentioning
confidence: 99%
“…As such, these findings also extend our understanding of the effect of COVID-19 on sustainable consumption. Despite other significant impacts reported for the COVID-19 pandemic (e.g., Li et al, 2021;Ozuem et al, 2021;Park, et al, 2022aPark, et al, , 2022b, empirical studies on its effect on consumption behavior are limited. Our results demonstrate that a high perceived threat of disease eliminates the impact of childhood socioeconomic status on sustainable consumption.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…Also, when a threat of disease is salient, individuals tend to avoid outgroups since outgroup members are more likely to transfer pathogens to which in‐group members do not have immunity yet (Fessler et al, 2005) and they may be perceived as a possible source of contamination (Terrizzi et al, 2013). Besides the interpersonal context, a recent study by Park et al (2022) in the context of COVID‐19 demonstrated that a heightened disease threat motivates people to lower their uncertainty and leads to increased preferences for products with authenticity appeals. Furthermore, research has shown that disease threat is related not only to outgroup avoidance strategies but also to ingroup approach strategies, such as conformity (Murray et al, 2011; Wu & Chang, 2012).…”
Section: Conceptual Backgroundmentioning
confidence: 99%